The use of confocal microscopy in quantifying changes in membrane potential - Elgar, D; Verdonck, F; Grobler, A; Fourie, C; Plessis, J D (African journal of biotechnology, 2006)
Monitoring the plasma membrane potential and its changes can be a time consuming and challenging task especially when conventional electrophysiological techniques are used. The use of potentiometric fluorophores, namely tetramethylrhodamine methylester (TMRM), and digital imaging devices (laser scanning confocal microscopy) provides reliable and time efficient method. Two scorpion pore-forming peptides, namely PP and OP1, were used as a tool to induce depolarization of the plasma membrane potential of neuroblastoma cell line and cardiac myocytes. Alternative methods for the neuroblastoma cells and cardiac myocytes were used. Depolarization of the neuroblastoma cells was calibrated with 140 mM KC1 solution with 1 mu M valinomycin, after which intensity readers were substituted in the Nernst equation for quantification. Calibration of the alternative method used of the cardiac myocytes' plasma membrane potential changes was calibrated with the use of 5, 20, 40, and 80 mM KC1 solutions with 1 mu M valinomycin. A calibration curve was then constructed from which plasma membrane potential could be calculated.